2020
DOI: 10.1002/rcr2.525
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab‐related pancreatitis with elevation of pancreatic tumour markers

Abstract: Lung cancer immunotherapy is an effective treatment option; however, it can be hampered by adverse events, including pancreatitis, associated with excessive immune activation. Here, we report the case of a 70-year-old patient who presented with recurrent lung squamous carcinoma and was started with pembrolizumab treatment (200 mg every three weeks). The patient developed pembrolizumab-induced pancreatitis. After 14 months of pembrolizumab treatment, positron emission tomography-computed tomography showed a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In both studies, no fatal case was reported. Our literature search found 12 case reports of ICI-induced pancreatitis ( Table ) ( 10 - 21 ), and all patients improved with cessation of the ICIs or corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, no fatal case was reported. Our literature search found 12 case reports of ICI-induced pancreatitis ( Table ) ( 10 - 21 ), and all patients improved with cessation of the ICIs or corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Abu-Sbeih et al ( 9 ) reported that more than half of ICI-related pancreatic injury cases were asymptomatic, and typical CT findings were present in only 25%, even among symptomatic patients. As illustrated in Table , ICI-related pancreatitis could be asymptomatic even with abnormal laboratory and radiological abnormalities ( 11 , 15 , 21 ). In our case, the diagnosis was not difficult to make because the patient had epigastric pain, elevated pancreatic enzyme values, and fluid collection around the enlarged pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of ICI-induced pancreatitis is lower than that of other irAEs, with its clinical characteris-tics still unclear, several case reports have been published (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Table shows the clinical characteristics of the 10 cases of ICI-induced pancreatitis that have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This result was also observed in previous studies of sclerosing cholangitis and pancreatitis. [13][14][15]23 Thus, irAE pancreatitis may have a good response to PSL, in contrast to cholangitis.…”
mentioning
confidence: 99%